The influence of provisioning on animal‐mediated seed dispersal. Issue 2 (29th April 2021) - Sengupta, Asmita; McConkey, Kim R.; Kwit, Charles
Abstract : Anthropogenic provisioning of food to wildlife is ubiquitous across the globe. It may be intentional such as in the form of bird feeders or offering of food to animals by tourists, or unintentional when animals use anthropogenic food sources like crops, plantations or garbage dumps. Provisioning has profound effects on wildlife ecology and behaviour, but the consequences of these changes to mutualistic and antagonistic interactions have rarely been investigated. Here we demonstrate how provisioning can affect the role of wildlife as seed dispersers. As provisioning directly influences the amount and quality of resources, it can substantially impact fruit removal by wildlife, seed displacement and the probability of germination at the sites of deposition – more often in ways that are detrimental. In most cases, fruit removal decreases as animals choose to feed more on the abundant and higher‐calorie anthropogenic foods. However, for animals whose size and abundance are increased by provisioning, dispersal quantity could be enhanced. Seed dispersal distances are also reduced by provisioning, and seeds are often deposited at sites unsuitable for germination. More studies are required to understand how these broad patterns might vary across different contexts and wildlife species. Provisioning has the potential to greatly modify plant communities through the direct impacts it has on resources and wildlife seed dispersal services.